Geochemical constraints on the origin of mafic rocks from the Cape Smith Belt - Hegner, E.; Bevier, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary The Trans-Hudson Orogen in Canada represents an early Proterozoic mountain belt similar to Phanerozoic orogens formed by plate tectonic processes. Volcanic rocks in northern Manitoba and Saskatchewan resemble island arc terranes, while continental rift and oceanic volcanic rocks dominate in the Cape Smith Belt in northern Quebec. Pb-Pb whole rock isotopic data for the ophiolitic Watts Group of the Cape Smith Belt yield an age of 1980 ± 30 Ma. Pb-Pb metamorphic (?) ages of 1890 Ma and 1700Ma were determined for rift-related igneous rocks of the Povungnituk Group and transitional volcanic rocks of the Chukotat Group, respectively. Sm-Nd isotopic compositionsare consistent with a magmatic evolution characterized by involvement of lithosphericmantle in Povungnituk Group volcanism, and depleted asthenospheric magmasources for MORB-like Chukotat Groupbasalts Sm-Nd isotopic compositions of the Watts Group show the characteristics of both Povungnituk and Chukotat Groupbasalts, suggesting similar sources.